Oracle8i DBA: Architecture & Administration Certification Bible - Bersinic Damir (Wiley, 2001)
This book delivers comprehensive coverage of exam objectives, presented according to Oracle's certification guide. Because Oracle's exam scoring provides section scores according to exact objectives, this organization of the book allows you to refocus. Each exam objective is covered in a chapter complete with self-assessment opportunities. Four appendices include a listing and description of Oracle's initialization parameters and other elements to be tested on the exam. These appendices provide information useful post-exam in real-work implementation of Oracle Systems.